PENANGGULANGAN MASALAH LINGKUNGAN HIDUP DI DESA KALAPANUNGGAL KABUPATEN SUKABUMI - Anne Sandra Dewi (STISIP Widyapuri Mandiri Sukabumi, 2025)
This community service program was carried out in Kalapanunggal Village, Sukabumi trough a series of environmental initiatives under the theme SAKU (Sampahku Karyaku), biopori infiltration holes and the construction of temporary waste disposal facilities. The program was designed to respond to the urgent environmental challenges faced by rural communities, particularly the lack of structured waste management systems. By combining education, practical training and participatory approaches, the program aimed to increase public awareness of waste sorting, promote creative waste recycling, and improve soil absorption capacity through biopori technology. The implementation involved 13 students of STISIP Widyapuri Mandiri Sukabumi and community members across different age groups. The results indicate that the community began to adopt new waste management practices, demonstrated by the creation of art products from waste, the establishment of biopore infiltration holes, and the utilization of temporary waste disposal sites. This program show that collaborative environmental initiatives not only improve ecological sustainability but also foster community empowerment.